1991
DOI: 10.1002/lary.5541011206
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and pneumococcal meningitis: An animal model

Abstract: Clinical studies of predisposing factors in the development of hearing loss secondary to bacterial meningitis have produced conflicting results. An animal model of meningogenic labyrinthitis was developed for more precise study of these parameters. Rabbits were inoculated intrathecally with 105 pneumococci to induce meningitis. Hearing thresholds were measured using auditory‐evoked responses to 1 kHz, 10 kHz, and click stimuli before infection and every 12 hours thereafter. Profound deafness occurred in all su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 27 publications
9
49
0
3
Order By: Relevance
“…Hearing loss results from involvement of the inner ear due to inflammation as pneumococci and leukocytes extend from the CSF to the perilymph via the cochlear aqueduct (4,5,11). In a model of pneumococcal meningitis the severity of permanent hearing impairment as assessed by the increase in the ABR thresholds 2 weeks after (20).…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss results from involvement of the inner ear due to inflammation as pneumococci and leukocytes extend from the CSF to the perilymph via the cochlear aqueduct (4,5,11). In a model of pneumococcal meningitis the severity of permanent hearing impairment as assessed by the increase in the ABR thresholds 2 weeks after (20).…”
Section: Discussionmentioning
confidence: 99%
“…Outbred strains, including Wistar, Sprague-Dawley, and CD (derived from Sprague-Dawley) rats, have been extensively utilized as experimental models (2,49,71,79,101,103,145,147,166,193,214,221,242,253). The New Zealand White rabbit is the most commonly used strain to induce pneumococcal pneumonia, sepsis, and meningitis (26,57,69,98,106,119,196,246). Finally, the chinchilla (only outbred strains are available), gerbil, and guinea pig are commonly used animal models of experimental otitis media (81,89,90,260).…”
Section: Considerations Of Animal and Pneumococcal Strainsmentioning
confidence: 99%
“…The availability of clinical isolates is also important in attempting the reproduction of human disease in laboratory animals. Several groups have preferred serotype 3 and 6 strains isolated from patients with pneumococcal meningitis and have successfully induced this disease in the mouse, the rat, and the rabbit (26,35,69,76,85,95,145,192,268,269). Clinical isolates of serotypes 3, 6, 9, and 19 have also been employed in laboratory animal models to elucidate features of pneumococcal pneumonia and sepsis (12,14,40,49,196,223,234,251).…”
Section: Considerations Of Animal and Pneumococcal Strainsmentioning
confidence: 99%
“…From human and animal studies, it can be shown that labyrinthitis can develop during bacterial meningitis, probably by bacteria reaching the perilymphatic channels via the cochlear aqueduct. [10][11][12] The resulting invasion may lead to destruction of the organ of Corti and calcification of the perilymphatic channels. Nitric oxide may contribute to mediating this injury as well.…”
Section: Pathophysiologymentioning
confidence: 99%